Understanding Teacher Identity Construction: Professional Experiences of Becoming Indonesian Montessori Teachers - Siswanto, Indira Lusianingtyas; Kuswandono, Paulus (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
This study sought to investigate the identity construction of Indonesian Montessori teachers. The research was done in two Montessori schools in Yogyakarta: Cosmic School and Universe School (pseudonyms). The participants involved in this research were eight teachers in total. The data gathering process employed questionnaire, classroom observation, interview, and written reflections. The findings have shed a light on the ways teachers develop their identities within Montessori’s values and principles that they reflect and implement in their daily teaching practice. The findings of the research portrayed that there were four major salient principles influencing the identity formation of becoming Montessori teachers. They were movement and cognition, choice, interest, and teacher ways and child ways. Those principles and values were becoming teachers’ guidance of creating professional working ethos. Montessori principles also influenced the teachers in the ways they perceived and treated the students. This study also revealed the undertaken agencies to hold identity as Montessori teachers. There were three broad themes to explain their agencies. They entailed the essence of building communication between teacher and parents, the significance of community support, and the importance of being well-prepared teachers. Based on the findings and discussion, some recommendations for future studies are also presented.